Effect of pulsed laser parameters on photoacoustic flow cytometry efficiency in vitro and in vivo - Grishin, Oleg V.; Shushunova, Natalia A.; Bratashov, Daniil N.; Prikhozhdenko, Ekaterina S.; Verkhovskii, Roman A.; Kozlova, Anastasiia A.; Abdurashitov, Arkady S.; Sindeeva, Olga A.; Karavaev, Anatoly S.; Kulminskiy, Danil D.; Shashkov, Evgeny V.; Inozemtseva, Olga A.; et al. (Cytometry. Part A)
Photoacoustic flow cytometry is one of the most effective approaches to detect "alien" objects in the bloodstream, including circulating tumor cells, blood clots, parasites, and emboli. However, the possibility of detecting high-amplitude signals from these objects against the background of blood depends on the parameters of the laser pulse. So, the dependencies of photoacoustic signals amplitude and number on laser pulse energy (5–150 μJ), pulse length (1, 2, 5 ns), and pulse repetition rate (2, 5, 10 kHz) for the melanoma cells were investigated. First, the PA responses of a melanoma cell suspension in vitro was measured to directly assess the efficiency of converting laser light into an acoustic signal. After it the same dependence with the developed murine model based on constant rate melanoma cell injection into the animal blood flow was tested. Both in vivo and in vitro experiments show that signal generation efficiency increases with laser pulse energy above 15 μJ. Shorter pulses, especially 1 ns, provide more efficient signal generation as well as higher pulse rates. A higher pulse rate also provides more efficient signal generation, but also leads to overheating of the skin. The results show the limits where the photoacoustic flow cytometry system can be effectively used for detection of circulating tumor cells in undiluted blood both for in vitro experiment s and for in vivo murine models.